ARMENIA: ON THE THORNY PATH TO INDEPENDENCE - MINASIAN, Edik (CENTRAL ASIA AND THE CAUCASUS, 2007)
The establishment or restoration of independence is the cherished desire and dream of every nation. During their multi-century history, the Armenian people have lost and restored their statehood many times. This also happened at the end of the 20th century, when a Third Republic was set up in Armenia. It was not only formed on the basis of the First (1918-1920) and Second (1920- 1991) republics, but also became their legal successor and heir. After existing for two and a half years, the First Republic laid the foundation for the Armenian state of the most recent period, essentially ensuring, albeit in imperfect form, its existence in the form of Soviet Armenia, which sometime later became part of the Transcaucasian Federation, and later of the U.S.S.R. As a constituent of the Soviet Union, the republic achieved significant success in almost all areas of social and economic life. It acquired a developed industry, agriculture, and culture, but it did not and could not become, a politically and economically independent, free national state. At the end of the 1980s-beginning of the 1990s, the U.S.S.R. fell apart as the result of the tempestuous development of political processes, and Armenia, along with the other Soviet republics, became independent, which was legislatively enforced on 21 September 1991 by the results of a national referendum.1 A presidential form of rule was introduced in Armenia In a short time, the Republic of Armenia (RA) acquired universal international recognition, became a member of the U.N., and established diplomatic relations with many countries of the world. At this time, the RA, like other post-Soviet republics, encountered the need from the very beginning to carry out significant changes throughout the system. These reforms encompassed all areas of society’s vital activity (political, economic, legal, social, cultural) and were very far-reaching and deepcutting in nature. Carrying out such transformations was unprecedented in its scope for the world community, that is, no other state had yet to resolve such major problems, and this meant there was no corresponding experience. In order to build a democratic, law-based state, it was necessary, in addition to carrying out political reforms, to proportionally and correctly develop different branches of the economy, replace ineffective management mechanisms with more effective market ones, and modernize the structure of the economy, adapting it to the needs created by the new economic system and producing goods and services that were competitive on the world market.